Crystal structure of bis[2-(1H-benzimidazol-2-yl-κN (3))aniline-κN]bis(nitrato-κO)cadmium(II) - Kim, Yongtae (Acta Crystallogr E Crystallogr Commun, 2019)
In the title compound, [Cd(NO(3))(2)(C(13)H(11)N(3))(2)], the Cd(II) atom lies on a twofold rotation axis and is coordinated by four N atoms and two O atoms, provided by two bidentate 2-(1H-benzimidazol-2-yl)aniline ligands, and two nitrato O atoms, forming a distorted octahedral geometry [range of bond angles around the Cd atom = 73.82 (2)–106.95 (8)°]. In the ligand, the dihedral angle between the aniline ring and the benzimidazole ring system is 30.43 (7)°. The discrete complex molecule is stabilized by an intramolecular N—H⋯O hydrogen bond. In the crystal, intermolecular N—H⋯O hydrogen bonds link the molecules, forming a three-dimensional network.